Upaya Pemberdayaan Minat Baca Masyarakat melalui Renovasi Pondok Baca di Desa Mekar Baru, Kec. Datuk Tanah Datar, Kab. Batubara: Pengabdian - Daulay, Khairnur Rahmah Diyah; Amalia, Annisa Rahma; Wijaya, Willy Gustira; Lubis, Fachrur Rozy; Andrianja, Syahvira; Tumanggor, Mutawaqil Billah; Harahap, Yulia Sari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The reading hut, which previously had limitations in terms of space comfort, layout, and minimal supporting facilities, was renovated to be more functional, attractive, and able to create a conducive learning atmosphere. The renovation included rearranging the interior, improving lighting, adding bookshelves, reading tables, and a multifunctional area that can be used for discussions and other literacy activities. The method used in this study was descriptive qualitative. Data were obtained through interviews, observation, and documentation. The results of this activity are expected to increase interest in reading, expand access to literacy, and make the reading hut a center of educational and social activities for the Mekar Baru Village community. This renovation also emphasizes the importance of collaboration between the community, village government, and related parties in supporting human resource development through the literacy movement